Mathematical modelling and morphological properties of thin layer oven drying of Vernonia amygdalina leaves - Alara, Oluwaseun Ruth; Nour, A. H.; Olalere, Olusegun Abayomi (Elsevier, 2017)
In this study, the oven drying behaviour, as well as changes in the morphological appearance of Vernonia amygdalina leaves before and after drying were investigated. The drying experiments were conducted using a universal oven. Vernonia amygdalina leaves were dried at 40, 50 and 60 °C air temperatures. During the drying processes, the air flow rate was held at 1 m/s2 and the samples spread on the drying trays were placed parallel to the direction of air flow. The obtained data were fitted to eleven different mathematical drying models. Four statistical tools, viz, correlation coefficient, mean bias error, sum of the square error, and reduced chi-square were used to analyse the fittings. Amongst the considered drying models, Midilli-Kucuk drying model showed the best fitting in describing the drying behaviour of Vernonia amygdalina leaves. In addition, the effective diffusivities for the three air temperatures ranged from 4.55 × 10−12 to 5.48 × 10−12 m2/s with the activation energy of 8.048 kJ/mol. Moreover, to evaluate the effect of drying conditions on the morphological changes of Vernonia amygdalina leaves, fresh and dried leaves under different conditions were compared. Thus, drying conditions had effects on microstructure of Vernonia amygdalina leaves.